2023
DOI: 10.1007/s40820-022-00994-3
|View full text |Cite
|
Sign up to set email alerts
|

Aerophilic Triphase Interface Tuned by Carbon Dots Driving Durable and Flexible Rechargeable Zn-Air Batteries

Abstract: Efficient bifunctional catalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are vital for rechargeable Zn-air batteries (ZABs). Herein, an oxygen-respirable sponge-like Co@C–O–Cs catalyst with oxygen-rich active sites was designed and constructed for both ORR and OER by a facile carbon dot-assisted strategy. The aerophilic triphase interface of Co@C–O–Cs cathode efficiently boosts oxygen diffusion and transfer. The theoretical calculations and experimental studies revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 85 publications
0
24
0
Order By: Relevance
“…From Figure S4d, the LED display can be lit up, which demonstrates the feasibility of the batteries in practical applications. In order to make a realistic comparison with previous materials, the characteristics of different robust catalysts for ZABs are summarized in Table . ,, The Co/N-C@NiCo 2 O 4 -based zinc–air batteries in this paper show excellent power density (176 mW cm –2 ) and good specific capacity and recycling performance. The comparison has confirmed that Co/N-C@NiCo 2 O 4 is a robust catalyst for synthesized ZABs.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure S4d, the LED display can be lit up, which demonstrates the feasibility of the batteries in practical applications. In order to make a realistic comparison with previous materials, the characteristics of different robust catalysts for ZABs are summarized in Table . ,, The Co/N-C@NiCo 2 O 4 -based zinc–air batteries in this paper show excellent power density (176 mW cm –2 ) and good specific capacity and recycling performance. The comparison has confirmed that Co/N-C@NiCo 2 O 4 is a robust catalyst for synthesized ZABs.…”
Section: Resultsmentioning
confidence: 99%
“…2,24 Reasonable construction of the surface structure of a bifunctional electrocatalyst to optimize the triple-phase interface is particularly useful for accelerating oxygen transfer and exposing more catalytic active sites, thereby promoting efficient and durable operation. 22,48,93,94…”
Section: Design Strategy For Advanced Bifunctional Oxygen Electrocata...mentioning
confidence: 99%
“…Very recently, Ding et al designed a bifunctional oxygen-respirable sponge-like Co@C-O-Cs electrocatalyst with oxygen-rich active sites via the assistance of carbon dots (CDs). 48 The high hydrophilicity and aerophilicity at the triple-phase interface induced fast O 2 diffusion and mass transfer, thereby providing excellent ORR/OER activity. The RZABs assembled with this kind of bifunctional electrocatalyst delivered a high peak power density (106.4 mW cm −2 ), large specific capacity (720.7 mA h g −1 ), and long-term cycle stability (over 750 cycles).…”
Section: Promoting Effect Triggered By Interfacial Regulationmentioning
confidence: 99%
“…Since then, developing fascinating CDs with versatile properties has received great attention in many fields. [7][8][9][10][11] The most predominant characteristic of CDs is that they have remarkable properties, such as tunable photoluminescence, 12 high fluorescence quantum yield (QY), 13,14 ease of surface functionalization, 15 good aqueous solubility, 16 superior biocompatibility, 17 and high photostability, 18,19 have received immense research attention, which enables CDs to be an excellent alternative to semiconductor quantum dots (QD) with a wide variety of promising applications in the fields of sensing, 20 bioimaging, 21 biomedicine, 22 electronic devices, 23 and anti-counterfeiting. 24 In the initial development stage of CDs, the main research focuses on the preparation of carbon dots, utilizing a large number of carbon sources and numerous approaches.…”
Section: Introductionmentioning
confidence: 99%